"Every Time I Try to Get Out, I Get Pushed Back"1: The Role of Violent Victimization in Women's Experience of Multiple Episodes of Homelessness. (September 2020) - Broll, Ryan; Huey, Laura
Research shows that, for most people, homelessness is not a chronic state that one enters and never leaves. Instead, homelessness tends to be dynamic, with individuals cycling in and out of multiple periods of homelessness throughout their lives. Despite this recognition, and a wealth of research on the causes of homelessness, generally, there is a lack of scholarship on the pathways to multiple episodes of homelessness. In particular, the relationship between violent victimization and women's likelihood of being homeless multiple times is largely unexplored. Drawing on data collected from 269 structured interviews conducted with women using the services of homeless shelters and/or transitional housing in three U.S. and two U.K. cities, we use multivariate logistic regression to assess whether violent victimization increases women's likelihood of experiencing multiple episodes of homelessness. Our results show that adult victims of stranger-perpetrated physical assault are significantly more likely to be homeless on multiple occasions. In addition, those who experience multiple forms of victimization (e.g., physical and sexual abuse) in childhood, adulthood, and/or across the life course are significantly more likely to experience multiple episodes of homelessness. Given recent efforts to eradicate homelessness, our results suggest specific vulnerable groups that may benefit from targeted social and policy interventions.